STRATEGI PEMBELAJARAN BERBASIS BLENDED LEARNING PADA PROGRAM STUDI PENDIDIKAN IPS FIS UNNES - Nisa, Aisyah Nur Sayidatun; Ginanjar, Asep (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2023)
The aim of this research is to find out what kind of support the Social Sciences EducationStudy Program provides as a policy maker in implementing blended learning-basedlearning strategies; to find out the extent of the use of blended learning-based technologyin the FIS UNNES Social Sciences Education Study Program; to analyze theimplementation of blended learning-based learning strategies in the FIS UNNES SocialSciences Education Study Program.The research method used is descriptive with a qualitative approach. The research subjectis the academic community of the Social Sciences Education Study Program. Datacollection through interviews, observation and documentation with data validity testingusing triangulation methods and data analysis techniques using interactive analysis.The results of the research found that the blended learning-based learning strategy in theFIS UNNES Social Sciences education study program was running well. Support fromlecturers, students, study program coordinators, faculties and universities really supportsthe implementation of this. One of the existing policies is the curriculum and supportinginfrastructure.